Extension of the CSM-FEMA440 to plan-asymmetric real building structures. - Bhatt, Carlos (Earthquake engineering & structural dynamics.)
The capacity spectrum method (CSM) has established itself as one of the most used Nonlinear Static Procedures for the seismic assessment of structures, since its introduction in 1975, when it was first presented by Freeman. More recently, this procedure was implemented in the ATC40 guidelines and lately improved in the FEMA-440 report. The first step of work addressed by this paper relates to the comparison between the two features of the CSM. In the second part, an extension of the FEMA-440CSM version is proposed for plan-asymmetric real RC building structures. The case studies under analysis are the SPEAR building-an irregular 3D structure representing typical old three storey buildings in the Mediterranean region, from the early 1970s-and two real Turkish buildings with five and eight storeys. The CSM-ATC40, the CSM-FEMA440 and the proposed extended CSM-FEMA440 method are applied and the results obtained duly compared with nonlinear dynamic timehistory analyses. For the latter, semi-artificial ground motions are used to define the seismic action.